The Effect of Corporate Tax Policy Reform on Investment Decisions and Profitability of Manufacturing Firms in Indonesia - Hariyanti Hariyanti; Ayu Esteka Sari; Toshniyozova Marjona Ikrom kizi (International Forum of Researchers and Lecturers, 2024)
This study examines the impact of tax policy reforms on investment decisions and profitability in Indonesia's manufacturing sector. Using panel data regression analysis over a five-year period, the research analyzes the relationship between tax reforms, investment behavior, and financial performance. The findings show that tax incentives significantly influence corporate investment decisions, with firms receiving tax relief increasing their capital expenditures by 12%. Additionally, these firms experienced a 15% increase in profitability, highlighting the importance of favorable tax policies in boosting firm performance. The study also finds that larger, capital-intensive firms benefit more from tax reforms, suggesting that firm characteristics play a crucial role in determining the effectiveness of tax incentives. The comparison of firms receiving tax relief versus those under standard tax rates further emphasizes the positive effects of tax incentives on investment and profitability. These results align with existing literature, which underscores the critical role of tax policy in promoting investment and long-term economic growth. However, the study also acknowledges certain limitations, including the sample size and the scope of data, and suggests future research should explore the broader effects of tax policies across various industries. The practical implications of the findings are significant for policymakers in Indonesia, as tax reforms can be a powerful tool for fostering economic growth and encouraging corporate investment in the manufacturing sector.